The Skeletal Effects of Short-Term Triple Therapy in a Rat Model of Gastric Ulcer Induced by Helicobacter pylori Infection - Ekeuku SO; Thong BKS; Quraisiah A; Annuar F; Hanafiah A; Nur Azlina MF; Chin KY (Dove Medical Press, 2020)
Sophia Ogechi Ekeuku,1 Benjamin Ka Seng Thong,1,2 Adam Quraisiah,1 Fazalda Annuar,1 Alfizah Hanafiah,3 Mohd Fahami Nur Azlina,1 Kok-Yong Chin1 1Department of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Cheras, Malaysia; 2Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Department of Medical Microbiology & Immunology Faculty of Medicine, Universiti Kebangsaan Malaysia, Cheras, MalaysiaCorrespondence: Kok-Yong ChinDepartment of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Level 17, Preclinical Building, Jalan Yaacob Latif, Bandar Tun Razak, Cheras 56000, Kuala Lumpur, MalaysiaTel +60 3-9145-9573Email chinkokyong@ppukm.ukm.edu.myPurpose: Triple therapy is the standard therapy to eradicate Helicobacter pylori (H.pylori) infection. Chronic use of proton pump inhibitors (PPIs), a component of triple therapy, is associated with osteoporosis. However, the skeletal effects of short-term triple therapy containing PPI remain elusive. This study aims to determine the skeletal effect of short-term triple therapy in a rat model of gastric ulcer induced by H. pylori.Methods: Three-month-old male Sprague Dawley rats were assigned to normal control, H. pylori-inoculated group (negative control) and H. pylori-inoculated group receiving triple therapy consisting of omeprazole [2.035 mg/kg body weight (b.w)], amoxicillin (102.80 mg/kg b.w) and clarithromycin (51.37 mg/kg b.w) (n=6/group). H. pylori infection developed for four weeks after inoculation, followed by two-week triple therapy. At the end of the treatment period, femoral bones of the rats were harvested for analysis. Bone mineral density and content of the femurs were determined using dual-energy X-ray absorptiometry, while bone strength was measured with a universal mechanical tester.Results: Bone mineral content was significantly lower in the negative control group compared to the triple therapy group (p=0.014). Triple therapy decreased strain (vs negative control, p=0.002) and displacement of the femur (vs normal control, p=0.004; vs untreated control, p=0.005). No significant difference was observed in other parameters among the study groups (p> 0.05).Conclusion: Short-term triple therapy increases bone mineral content but decreases bone strength of rats. Skeletal prophylaxis should be considered for patients on short-term triple therapy containing PPI.Keywords: bone, gastric ulcer, omeprazole, osteoporosis, osteopenia, proton pump inhibitor